(untitled) (The International Journal for Scientific Research, 2026)
This research aims to extract oil from the seeds of the neem tree (Azadirachta indica) and study its application as a pesticide for stored-product pests. The oil was extracted from the neem tree seed at a rate of 55.41% using continuous extraction technology and ordinary hexane as a solvent. Neem oil extract was applied as a pesticide against the Khapra beetle, which is one of the most common pests attacking white corn. The study was conducted at the Environment and Natural Resources Research Center in Khartoum-Sudan by treating 18 plates of stored white corn. 6 plates were used as a control, 3 of which contained seeds not treated with oil and soap, and 3 other plates containing white corn seeds treated with soap and water. The remaining plates contained seeds treated with different concentrations of extracted oil (25.0%, 5.0%, 1%, and 2%) after treatment with a small amount of soap. Ten larvae of the Khapra beetle were placed in each plate to monitor the lethal effect and feeding. This was achieved by placing 10 khapra beetle larvae in each dish to monitor the insecticidal effect and feeding, and 30 khapra beetle larvae to monitor the repellent effect. The study was conducted for seven days, during which the effect of the extracted oil on the repellent, insecticidal, and feeding rates of the khapra beetle larvae was observed. The results showed that it was effective in repelling insects, increasing insecticidal activity, and promoting feeding at concentrations of 25.0%, 5.0%, 1%, and 2%, with the 2% concentration yielding the best results. When comparing the 2% concentration with the untreated seeds with the extracted oil and liquid soap, it also became clear that it was more effective in repelling insects, as 17 healthy corn seeds were observed out of 20 seeds after three months from the beginning of the experiment, while the untreated seeds showed no seeds after one month from the beginning of the experiment. Hence the importance of this research lies in finding natural alternatives to manufactured pesticides in the field of agricultural pest control, "stored pests," as they can be more effective and feasible, and have no harm to humans or living organisms, and are also economically inexpensive.